PENGARUH PENGGUNAAN MEDIA E-BOOK INTERAKTIF BERBASIS CANVA TERHADAP PEMAHAMAN NILAI PERSATUAN KESATUAN SISWA KELAS IV SD GUGUS X KOTA BENGKULU - Winda, Risma; Susanti, Atika; Kurniawati, Ike (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using Canva-based interactive e-book media on the understanding of the value of unity and oneness of fourth-grade students of Elementary School Cluster X, Bengkulu City. This type of research is quantitative research and the research method used is a quasi-experimental method, with the research design used is the Matching Only Pretest-Posttest Group Design. The population in this study was SDN Cluster X, Bengkulu City. The sample in this study was taken using the Cluster Random Sampling technique, so that fourth-grade students of SDN 32, Bengkulu City were obtained as the experimental group using Canva-based interactive e-book media and fourth-grade students of SDN 15, Bengkulu City as the control group using printed Pancasila education books. The research instrument used was a written test with 16 multiple-choice questions with data collection techniques in the form of a pretest and posttest. Data analysis used in this study was descriptive analysis, swimmer tests, and inferential analysis, namely the t-test. The results of this study showed a significant difference between the average scores in the experimental group and the control group. These results are proven by the calculated t value = 2.831 Sig. (2-tailed) is 0.006 and the t table distribution value is 2.005 so that the calculated t value > t table (2.831 > 2.005) and Sig. (2-tailed) is 0.006 < 0.005. Therefore, Ho is rejected and Ha is accepted. This is based on the difference in treatment between the experimental group and the control group. Thus, from the results of this study, it can be concluded that there is an effect of the use of interactive e-book media on the understanding of the value of unity of fourth-grade students of Elementary School Cluster X, Bengkulu City. Keywords: interactive e-book media1, Canva2, understanding the value of unity3